Benzodiazepines for antipsychotic‐induced tardive dyskinesia - Bergman, Hanna (Cochrane Database Syst Rev, 2018)
BACKGROUND: Tardive dyskinesia (TD) is a disfiguring movement disorder, often of the orofacial region, frequently caused by using antipsychotic drugs. A wide range of strategies have been used to help manage TD, and for those who are unable to have their antipsychotic medication stopped or substantially changed, the benzodiazepine group of drugs have been suggested as a useful adjunctive treatment. However, benzodiazepines are very addictive. OBJECTIVES: To determine the effects of benzodiazepines for antipsychotic‐induced tardive dyskinesia in people with schizophrenia, schizoaffective disorder, or other chronic mental illnesses. SEARCH METHODS: On 17 July 2015 and 26 April 2017, we searched the Cochrane Schizophrenia Group's Study‐Based Register of Trials (including trial registers), inspected references of all identified studies for further trials and contacted authors of each included trial for additional information. SELECTION CRITERIA: We included all randomised controlled trials (RCTs) focusing on people with schizophrenia (or other chronic mental illnesses) and antipsychotic‐induced TD that compared benzodiazepines with placebo, no intervention, or any other intervention for the treatment of TD. DATA COLLECTION AND ANALYSIS: We independently extracted data from the included studies and ensured that they were reliably selected, and quality assessed. For homogenous dichotomous data, we calculated random effects, risk ratio (RR), and 95% confidence intervals (CI). We synthesised continuous data from valid scales using mean differences (MD). For continuous outcomes, we preferred endpoint data to change data. We assumed that people who left early had no improvement. MAIN RESULTS: The review now includes four trials (total 75 people, one additional trial since 2006, 21 people) randomising inpatients and outpatients in China and the USA. Risk of bias was mostly unclear as reporting was poor. We are uncertain about all the effects as all evidence was graded at very low quality. We found no significant difference between benzodiazepines and placebo for the outcome of 'no clinically important improvement in TD' (2 RCTs, 32 people, RR 1.12, 95% CI 0.60 to 2.09, very low quality evidence). Significantly fewer participants allocated to clonazepam compared with phenobarbital (as active placebo) experienced no clinically important improvement (RR 0.44, 95% CI 0.20 to 0.96, 1 RCT, 21 people, very low quality evidence). For the outcome 'deterioration of TD symptoms,' we found no clear difference between benzodiazepines and placebo (2 RCTs, 30 people, RR 1.48, 95% CI 0.22 to 9.82, very low quality evidence). All 10 participants allocated to benzodiazepines experienced any adverse event compared with 7/11 allocated to phenobarbital (RR 1.53, 95% CI 0.97 to 2.41, 1 RCT, 21 people, very low quality evidence). There was no clear difference in the incidence of participants leaving the study early for benzodiazepines compared with placebo (3 RCTs, 56 people, RR 2.73, 95% CI 0.15 to 48.04, very low quality evidence) or compared with phenobarbital (as active placebo) (no events, 1 RCT, 21 people, very low quality evidence). No trials reported on social confidence, social inclusion, social networks, or personalised quality of life, which are outcomes designated important by patients. No trials comparing benzodiazepines with placebo or treatment as usual reported on adverse effects. AUTHORS' CONCLUSIONS: There is only evidence of very low quality from a few small and poorly reported trials on the effect of benzodiazepines as an adjunctive treatment for antipsychotic‐induced TD. These inconclusive results mean routine clinical use is not indicated and these treatments remain experimental. New and better trials are indicated in this under‐researched area; however, as benzodiazepines are addictive, we feel that other techniques or medications should be adequately evaluated before benzodiazepines are chosen.